Local government strategy in managing traditional markets in the city of Pariaman, Indonesia - Herza Netti; Erianjoni Erianjoni (Otoritas : Jurnal Ilmu Pemerintahan, 2023)
The rationale for conducting this research stems from the observation that the government's efforts in administering the Pariaman traditional market have not been fully optimised, leading to inefficient development strategies aimed at enhancing the regional revenue of Kota Pariaman. The objective of this study is to examine the local government's approach to administering traditional markets in Pariaman City, Indonesia. The present study employs qualitative research methodology, specifically utilising descriptive methodologies. The application of SWOT analysis was employed throughout the many stages of data processing, data analysis, data reduction, and drawing conclusions. The results of this study indicate that (1) infrastructure facilities such as playgrounds can be an attraction for, (2) good organizational governance, (3) Being able to create tourism-based innovations, (4) Providing freedom to rent shops for yellow card owners so that they get full benefits from the sales proceeds, (5) conduct socialization to all yellow card owners, (6) carry out repairs to leaky buildings, (7) conduct training to improve employee performance, (8) make regulations regarding shop rental fees, (9) improve supervision so that visitors are more comfortable, (10) Improve facilities and infrastructure in traditional markets in dealing with home industry (11) Involving security officers to carry out their functions in controlling morning market traders and street vendors around Pariaman tradisional market, (12) taking action against elements who set prices for renting kiosks outside the arena (13) increased supervision. it can be interpreted that the Pariaman government needs to take better steps and strategies.